2013
DOI: 10.1371/journal.pone.0059419
|View full text |Cite
|
Sign up to set email alerts
|

Functional Impact of ABCB1 Variants on Interactions between P-Glycoprotein and Methadone

Abstract: Methadone is a widely used substitution therapy for opioid addiction. Large inter-individual variability has been observed in methadone maintenance dosages and P-glycoprotein (P-gp) was considered to be one of the major contributors. To investigate the mechanism of P-gp’s interaction with methadone, as well as the effect of genetic variants on the interaction, Flp-In™-293 cells stably transfected with various genotypes of human P-gp were established in the present study. The RNA and protein expression levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 48 publications
(65 reference statements)
4
29
0
Order By: Relevance
“…There was no significant difference among the mRNA and protein expression levels of wild type ABCB1 and the two variant types as showed in our previous studies [16], [17]. After 72 hours treatment of 5 µg/mL EEAC, the ABCB1 mRNA and protein expression remained unchanged in wild type ABCB1 and the two variant types (Fig.…”
Section: Resultssupporting
confidence: 58%
“…There was no significant difference among the mRNA and protein expression levels of wild type ABCB1 and the two variant types as showed in our previous studies [16], [17]. After 72 hours treatment of 5 µg/mL EEAC, the ABCB1 mRNA and protein expression remained unchanged in wild type ABCB1 and the two variant types (Fig.…”
Section: Resultssupporting
confidence: 58%
“…A more recent in vitro study utilizing cells stably transfected with various genotypes of ABCB1 (P-gp) found that methadone most potently inhibited wild-type P-gp (IC 50 =2.17 μM), while the genotypes 1236T-2677T-3435T (IC 50 = 2.97 μM) and 1236T-2677A-3435T (IC 50 =4.43 μM) exhibited much less inhibition. The study also confirmed that methadone stimulated P-gp ATPase activity and inhibited verapamil (145).…”
Section: Methadonesupporting
confidence: 72%
“…However, recent research suggests that the large inter-individual variability in methadone dose may be influenced by an interactions between ABCB1 polymorphisms and p-glycoproteins [53]. Most recent investigations into this area are limited by the lack of available clinical populations; further evidence is required to examine this interaction.…”
Section: Discussionmentioning
confidence: 99%